DISKRIMINASI TERHADAP PENDIDIKAN ISLAM DI INDONESIA: Latar Belakang Muncul dan Upaya Menghilangkannya - Anhar Anhar (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2009)
Islamic education in Indonesia does not recognize dichotomy system despite the fact that, historically, the dichotomy between secular education and Islamic education in the colonial era did exist. It is claimed that the dichotomy between the two areas is more of a discriminative issue. One alternative solution to this is an integrated model, where centralized management of Islamic education by the Ministry of Religious Affairs and the secular education under the management of the ministry of the national education, to be handled by the local government. This is in accordance with the National Constitution no. 32, 2004 about local government.